Ecolinguistic Approach to Online Finnish Discourse on Invasive Alien Species - Uusitalo Harri; Suomalainen Karita (Germany, 2025)
This ecolinguistic article investigates how alien species are perceived in mundane interactions in Finnish online discussions, based on data collected from the popular Finnish Suomi24 online discussion forum. We ask: What organisms does the lexical item vieraslaji ‘alien species’ cover for the forum participants, and what kinds of discourses are built around the term vieraslaji? The results of digital content analysis and discourse analysis show that nonhuman animals and humans are much more common topics than plants; this indicates that the nature discourse related to alien species is animal centered and that certain species dominate the discussions. The lexical item vieraslaji is used in affective contexts, reflecting the fact that discussion of invasive species is emotionally laden. Our analysis also reveals that the discursive features of online discussions on invasive species show similarities with online anti-immigration hate speech discourse, and that xenophobic discourse is partially inspired by the nature discourse. Based on these results, we argue that a more diverse discussion about alien species is needed.